Misogynistic Hadith in Daud Rasyid's Perspective: Rejection of Feminist Narratives - Muhid; rahma, Dinda Syarifaturrahma; Ahmad Aminuddin Widodo (Medina-te : Jurnal Studi Islam, 2024)
This study examines the criticism delivered by Daud Rasyid against a number of Hadiths that are considered to contain misogynistic views, with the main focus on his response to the feminist interpretations put forward by Riffat Hassan and Wardah Hafiz. The main objective of this study is to refute feminist views that often degrade the dignity of women, especially related to the narrative that mentions the creation of women from the ribs of men and the comparison of women with animals in the context of prayer. This study uses a qualitative method with a descriptive case study approach, in which Daud Rasyid's work, Sunnah Under Threat, is analyzed in depth along with relevant secondary data. The results of the study show that Daud Rasyid argues that the Hadiths that have been considered as evidence of women's inferiority actually describe a complementary relationship between men and women, not a relationship that places women in a lower position. In addition, Daud Rasyid also provides a contextual interpretation related to the disruption of prayer by women, donkeys, and dogs, which is interpreted as reducing the quality of prayer, not canceling it. This study also emphasizes the importance of contextual understanding in interpreting Hadith, as well as the need to respect traditional methodology in Hadith studies. Overall, the results of this study indicate that with a deeper and contextual understanding, Hadith can be interpreted more fairly and wisely, giving women a more equal position in the religious perspective.